2012
DOI: 10.3892/ijo.2012.1349
|View full text |Cite
|
Sign up to set email alerts
|

Crucial cross-talk of interleukin-1β and progesterone in human choriocarcinoma

Abstract: Abstract. Choriocarcinoma is a highly malignant epithelial tumour that is most often associated with hydatidiform mole and presents the most common emergency medical problem in the management of trophoblast disease. We hypothesise that the hormones/cytokines present within the tumour microenvironment play key roles in the development of choriocarcinoma. In this study we assessed the effects of interleukin-1β (IL-1β) on cell death in the presence or absence of the sex hormone progesterone using two choriocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Our work indicated that progesterone could activate the ERK1/2 pathway and, thus, significantly increase the expression of EZH2 accompanied with the decreased level of CDX1, but not the PI3K/AKT signaling pathway. This is in accordance with the results that report that progesterone is able to induce phosphorylation of ERK1/2 in two choriocarcinoma cell lines (BeWo and JEG-3) 49 and is consistent with the reports demonstrating that the phosphorylation of EZH2 at serine 21 suppresses its methyltransferase activity responsible for H3-K27 trimethylation 50, 51. The decreased expression of EZH2 in women with RM provides new insights into the epigenetic mechanisms underlying the pathogenesis of RM and paves new avenues for the development of novel therapeutics.…”
Section: Discussionsupporting
confidence: 93%
“…Our work indicated that progesterone could activate the ERK1/2 pathway and, thus, significantly increase the expression of EZH2 accompanied with the decreased level of CDX1, but not the PI3K/AKT signaling pathway. This is in accordance with the results that report that progesterone is able to induce phosphorylation of ERK1/2 in two choriocarcinoma cell lines (BeWo and JEG-3) 49 and is consistent with the reports demonstrating that the phosphorylation of EZH2 at serine 21 suppresses its methyltransferase activity responsible for H3-K27 trimethylation 50, 51. The decreased expression of EZH2 in women with RM provides new insights into the epigenetic mechanisms underlying the pathogenesis of RM and paves new avenues for the development of novel therapeutics.…”
Section: Discussionsupporting
confidence: 93%
“…Based on accumulating evidence, alveolar macrophages (AMOs) are the effector cells of silicosis 3 , 5 , 20 . AMOs are the most important immune barrier against invading pathogens and environmental contaminants in pulmonary innate immunity 14 , 21 . Thus, the effect of SiO 2 on circHECTD1 expression was measured in mouse RAW264.7 macrophages.…”
Section: Resultsmentioning
confidence: 99%